Epidemiological Patterns of Central Nervous System Neoplasms in Brazilian Vulnerable Children - Andre Akira Ramos Takahashi; Livia Akemi Ramos i Takahash; Sandra Di Felice Boratto; Leonardo Alfano de Lima; Laercio da Silva Paiva; Stefanie de Sousa Antunes Alcantara; Luiz Vinicius de Alcantara Sousa (European Scientific Journal, ESJ, 2020)
Introduction: Central nervous system (CNS) neoplasms are the most common solid tumors within the pediatric population, being an important cause of death and functional losses in this age group. Although studies show that there is good evolution and adaptation of pediatric survivors in adulthood, the interaction of these individuals with social inclusion factors still worries the medical environment. Objective: To analyze the temporal trend of mortality, hospitalization and social vulnerability of children with CNS Neoplasia and correlate with social indicators. Methods: An ecological study carried out in November 2018, through the analysis of secondary data on mortality, hospital admission, social vulnerability index and social indicators of Brazil, collected in DATASUS, and the Atlas of Social Vulnerability available at the Institute of Economic Research in the period from 2010 to 2015. Results: The improvement of social variables in all Brazilian regions; There was an increase in hospitalizations for Nervous System neoplasms for the 5 to 9-year-old male in the Northeast region; To the North, in the age group 0 to 4 years the hospitalization rates were positively correlated with the IVS, negatively with the HDI and positively with the Gini index; It was possible to identify a negative correlation between the IVS and the total number of hospitalizations for the Northeast in the female sex; Regarding mortality, there was a positive correlation between total mortality and IVS in the Midwest for the male population. Conclusion: It was concluded that there was a correlation between the various social indexes (HDI, IVS and Gini index) and the incidence and mortality due to Central Nervous System neoplasms in the pediatric population.